A risk assessment indicator system for common diseases in children and adolescents - Yun Shao; Bohan Hu; Yuting Lu; Shuo Yu; Ji Liang (PLoS ONE, 2026)
Background Adolescence is a critical stage for healthy development. Currently, common diseases such as myopia, obesity, dental caries, and spinal curvature abnormalities are highly prevalent among children and adolescents, with an obvious trend of younger onset. These diseases are caused by the complex interaction of multi-dimensional factors. However, existing interventions are mostly limited to individual diseases, lacking systematic prevention and control tools. Therefore, there is an urgent need to construct a scientific evaluation index system for health-influencing factors. Objective Targeting the four key common diseases emphasized in China’s national health policies – myopia, obesity, dental caries, and spinal curvature abnormalities – among children and adolescents aged 7–19 years, this study constructed a multi-dimensional risk assessment indicator system to support evidence-based prevention and policy-making for this population. Methods Guided by the National Program of Action for Children’s Development in China (2021–2030) and the “Healthy China 2030” Planning Outline, a three-level indicator framework was initially formulated through literature research and expert meetings. The Delphi expert consultation method was adopted for two rounds of screening and optimization of indicators. Experts scored each indicator on a scale of 1–5 in terms of importance, feasibility, and sensitivity, with indicators excluded if their mean score was < 3.5 and coefficient of variation >0.3. Results The effective return rate of the two-round Delphi is 100.0%, the mean expert familiarity coefficient (Cs) was 0.83, and the mean judgment coefficient (Ca) was 0.93, and the expert authoritative coefficient (Cr) value is 0.88. In the second round of consultation, the importance coordination coefficient is 0.284, the feasibility coordination coefficient is 0.185, and the sensitivity coordination coefficient is 0.314, all of which are statistically significant ( P < 0.001). This indicator system consists of a total of 55 three-level indicators. Conclusion Validated through two rounds of expert deliberation, the indicator system demonstrates sound scientific rigor. The preliminary development of a risk assessment indicator system for common diseases in children and adolescents can be used for the measurement of the level of factors affecting the health of common diseases in children and adolescents after its reliability and validity are verified in practical applications.